Alphabetic print-based literacy, hermeneutic sociality, and philosophic culture. Issue 4 (2nd October 2017) - Anton, Corey
ABSTRACT: This essay offers a media ecological orientation to Western philosophy, showing the essential role that alphabetic writing and print play in making philosophy possible. It offers reviews of historical developments in alphabetic print-based literacy to show how modern literacy has congealed into a hermeneutic sociality undergirding philosophic culture.